Prevalence of potential candidates for electric-acoustic stimulation implant in a hearing-impaired population. Issue 2 (April 2020) - Saito, Kazuya; Fujita, Takeshi; Osaki, Yasuhiro; Koyama, Hajime; Shiraishi, Ko; Kobayashi, Takaaki; Sato, Mitsuo; Seo, Toru; Doi, Katsumi
Abstract: Objective: To estimate the prevalence of potential electric-acoustic stimulation (EAS) implant candidates in a hearing-impaired population through a review of auditory examinations. Methods: In total, 7356 patients underwent audiometric examination in our department between 2011 and 2014. The prevalence of patients meeting the audiometric criteria for EAS and standard cochlear implant (CI) was assessed. Results: The percentage of EAS implant candidates meeting the pure-tone audiometric criteria was 0.71% (n = 34) among the hearing-impaired individuals (n = 4758) examined in our department, whereas 2.52% (n = 120) met the criteria for standard CI. Among the 34 EAS implant candidates, 2 individuals (5.83%) received EAS implant surgery after approval of the EAS device in Japan. Conclusions: There was a lower prevalence of EAS implant candidates than standard CI candidates. Nevertheless, healthcare professionals should carefully examine the audiograms of patients with high frequency hearing loss with regard to meeting the indication criteria for EAS implant. This will enable patients to gain access to adequate information relating to further examinations and treatment options.